The impact of cerebrospinal fluid viral polymerase chain reaction testing on the management of adults with viral meningitis: A multi‐center retrospective study. Issue 1 (13th October 2022) - Kim, Myong Gyu; Gulholm, Trine; Lennard, Kate; Mirdad, Feras; Overton, Kristen; Maley, Michael; Konecny, Pamela; Andresen, David; Post, Jeffrey John; ,
Abstract: The aim of this study was to evaluate the role of viral polymerase chain reaction (PCR) testing in patients with aseptic meningitis and identify opportunities for improvement in clinical management. All cerebrospinal fluid samples collected in 1 year from four teaching hospitals in Sydney, Australia, were reviewed. Patients with aseptic meningitis were selected, and clinical and diagnostic features, hospital length of stay (LOS), and treatment were analyzed. Identifying a cause by viral PCR did not reduce hospital LOS (median 3 days) or antibiotic use (median 2 days), but the turnaround time of the PCR test correlated with LOS (Rs = 0.3822, p  = 0.0003). Forty‐one percent of patients received intravenous acyclovir treatment, which was more frequent in patients admitted under neurologists than infectious diseases physicians (56% vs. 24%; p  = 0.013). The majority of patients did not have investigations for alternative causes of aseptic meningitis such as human immunodeficiency virus and syphilis if the viral PCR panel was negative. The benefit of PCR testing in aseptic meningitis in adults in reducing LOS and antibiotic use is unclear. The reasons for unnecessary aciclovir use in meningitis syndromes require further assessment.